RANCANG BANGUN ALAT PEMBERIAN PAKAN IKAN OTOMATIS BERBASIS ANDROID DAN SOLAR CELL DI DAERAH TIMBAK IKAN KABUPATEN KAMPAR - Frensis Owen; Mochamad Susantok (ABEC Indonesia, 2021)
In the fish farming business, feeding is very important. This causes fish entrepreneurs to try to be effective in feeding by employing other people to feed the fish. However, workers cannot spend 24 hours in the pond, so an automatic feed spreader is needed to make it easier for workers and ease the burden on fish entrepreneurs. This automatic feed spreader is designed using solar energy. This study uses NodeMCU ESP8266 as a microcontroller. The resulting data are in the form of average feed output, feed output per second, distance of feed throw, the effectiveness of tools in large ponds, and the time required for the solar cell to charge the battery and battery life in normal conditions. The average output test obtained is 1403.8 gr, the average feed output per second is 561.52 gr / s, the measurement of the farthest throw distance is 5 m when the tool is placed on a 30 cm high support and from the data obtained by the tool This automatic feeder is effective against all types of pond sizes, namely small, medium and large ponds. Then in terms of solar cells, the time needed to charge the battery capacity is 2-3 hours and the resistance of the tool in normal conditions is up to 12 hours. With this tool, fish feed can be done more optimally and in a more timely manner and provides convenience for fish breeders in terms of feeding.